Enhance Customer Satisfaction in An Indonesian Cargo Service Company - Kasmad Kasmad; Yuditio Yuditio (Majalah Ilmiah Bijak, 2025)
This study aims to determine a more appropriate marketing strategy at PT. Amanah Cargo Jaya Mandiri in order to increase customer satisfaction. The method used in this study is a qualitative method with IFE, EFE, IE, and SWOT (Strength, Weakness, Opportunities, Threats) analysis.The results of the study indicate that the marketing strategy implemented by PT. Amanah Cargo Jaya Mandiri is able to increase customer satisfaction but additional strategies are needed to increase customer satisfaction. PT. Amanah Cargo Jaya Mandiri is in a good position, has opportunities, and is able to continue to expand and provide better services in order to increase customer satisfaction and increase growth in order to obtain maximum profit.